MicroRNAs in Serum Exosomes as Circulating Biomarkers for Postmenopausal Osteoporosis - Shi, Hongli; Jiang, Xin; Xu, Cuidi; Cheng, Qun (Frontiers in Endocrinology, 2022)
Postmenopausal osteoporosis (PMOP) is the most common skeletal disease in postmenopausal women and has become a global public health issue. Emerging evidence demonstrated the important relationship between microRNAs and PMOP. However, miRNAs have not yet been reported in PMOP. Hence, the present study aimed to investigate the differences in miRNA expression profiles in PMOP with fragility fractures to identify the key circulating miRNAs in serum exosomes and to validate these molecules as potential biomarkers. Postmenopausal women with osteoporotic fracture and normal bone mass were enrolled. Serum exosomes were isolated by traditional differential ultracentrifugation from participants. Isolated exosomes were identified by electron microscopy, western blotting and nanoparticle-tracking analysis and then examined for exosomal small RNA sequencing. The expression of miRNAs was compared by sRNA deep sequencing and bioinformatics analysis. Three miRNAs (miR-324-3p, miR-766-3p and miR-1247-5p) were found to be associated with BMD of L1-L4, FN and TH, while miR-330-5p and miR-3124-5p were associated with BMD of FN and TH. Furthermore, miR-330-5p was found to promote the ALP activity of hBMSCs, while mir-3124-5p showed the opposite result. The results showed that serum exosomal miRNAs were differentially expressed in postmenopausal osteoporosis patients with fragility fractures. Our study provides the first evidence that exosomal miRNA profiling revealed aberrant circulating miRNA in postmenopausal osteoporosis. MiR-324-3p, miR-766-3p, miR-1247-5p, miR-330-5p, and miR-3124-5p, which were associated with BMD, may serve as candidate diagnostic biomarkers as well as potentially contribute to the pathophysiology of PMOP.